1993
DOI: 10.1159/000282475
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Changes in Parameters of the Coagulation and Fibrinolysis in Association with Extracorporeal Shock Wave Lithotripsy

Abstract: Tissue damage by extracorporeal shock wave lithotripsy (ESWL) is assumed to be attributable to ischemic changes in the treated region surrounding the particular vessel which is first ruptured by shock waves. Such changes cannot take place without being accompanied by acceleration of coagulation and fibrinolysis. In the literature on renal damage by ESWL, no parameters of the coagulation and fibrinolysis of blood were used. The present study was designed to investigate renal damage by shock waves through the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
3
2
0
Order By: Relevance
“…D-dimer concentration, in nephrolithiasis patients following ESWL, compared to healthy subjects and patients undergoing ESWL. These observations were similar to those of Umekawa et al [ 2 ] and Hughes et al [ 3 ]. Umekawa et al [ 2 ] report a correlation between fibrin degradation products (FDP) and D-dimer concentration following SWL.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…D-dimer concentration, in nephrolithiasis patients following ESWL, compared to healthy subjects and patients undergoing ESWL. These observations were similar to those of Umekawa et al [ 2 ] and Hughes et al [ 3 ]. Umekawa et al [ 2 ] report a correlation between fibrin degradation products (FDP) and D-dimer concentration following SWL.…”
Section: Discussionsupporting
confidence: 93%
“…These observations were similar to those of Umekawa et al [ 2 ] and Hughes et al [ 3 ]. Umekawa et al [ 2 ] report a correlation between fibrin degradation products (FDP) and D-dimer concentration following SWL. Interestingly, our present findings do not include any significant changes in PT, TT or APTT in patients with nephrolithiasis, either before or after ESWL.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Measurement of D-dimer, which is a marker of haemostatic activity, showed a significant increase in concentration following SWL (p = 0.019). These observations were similar to those of Umekawa et al (1993), who reported a transient acceleration in fibrin degradation products (FDP) and D-dimer levels following SWL [ 20 ]. Interestingly, no significant changes were observed in the PT and aPTT following SWL, although fibrinogen concentration decreased significantly (p = 0.014).…”
Section: Discussionsupporting
confidence: 90%